Asetilasi Kayu Rambutan (Nephelium lappaceum L), Cempedak (Artocarpus integer Merr), dan Rambai (Baccaurea montleyana Muell. Arg) - Jendro Zalukhu; Luthfi Hakim; Rudi Hartono (Program studi Kehutanan USU, 2012)
The utilization of fruit woods increased according of increasing human needs. Several weakness of fruit woods were bad dimensional stability and susceptible wood from termite attack. Preservation can improve the dimensional stability and increase the wood from termite attack. One preservation method of was acetylation. The research purpose were to known the effect of rambutan, cempedak and rambai woods variety and acetic acid concentration to retention value, to evaluated the dimention stability and Weight Percent Gain and to evaluated durability from attack termite based on graveyard test and laboratory test. Some kind of wood such as rambutan, cempedak and rambai woods were treated by soaking during 2 weeks with acetic acid concentration of 10%, 15%, 20% and 25%. The results showed the effective retention on rambai wood with concentration of 20% was 3.81%. The high dimention stability ASE on rambutan wood with concentration of 15% was 73.37%, and the high WPG on rambai wood with concentration of 25% was 46.66%. The increasing of acetid acid concentration caused the increasing retention and wood resistance from termite attack in graveyard test and laboratory test. Key words: Wood, acetylation, ASE, WPG, termite